Priming With Rhinovirus Protects Mice Against a Lethal Pulmonary Coronavirus Infection - Cox, Garrison; Gonzalez, Andres J.; Ijezie, Emmanuel C.; Rodriguez, Andres; Miller, Craig R.; Van Leuven, James T.; Miura, Tanya A. (Frontiers in Immunology, 2022)
Rhinoviruses (RV) have been shown to inhibit subsequent infection by heterologous respiratory viruses, including influenza viruses and severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). To better understand the mechanisms whereby RV protects against pulmonary coronavirus infection, we used a native murine virus, mouse hepatitis virus strain 1 (MHV-1), that causes severe disease in the lungs of infected mice. We found that priming of the respiratory tract with RV completely prevented mortality and reduced morbidity of a lethal MHV-1 infection. Replication of MHV-1 was reduced in RV-primed mouse lungs although expression of antiviral type I interferon, IFN-beta, was more robust in mice infected with MHV-1 alone. We further showed that signaling through the type I interferon receptor was required for survival of mice given a non-lethal dose of MHV-1. RV-primed mice had reduced pulmonary inflammation and hemorrhage and influx of leukocytes, especially neutrophils, in the airways upon MHV-1 infection. Although MHV-1 replication was reduced in RV-primed mice, RV did not inhibit MHV-1 replication in coinfected lung epithelial cells in vitro. In summary, RV-mediated priming in the respiratory tract reduces viral replication, inflammation, and tissue damage, and prevents mortality of a pulmonary coronavirus infection in mice. These results contribute to our understanding of how distinct respiratory viruses interact with the host to affect disease pathogenesis, which is a critical step in understanding how respiratory viral coinfections impact human health.